Pengaruh Daya Tarik , Aksesbilitas Dan Fasilitas Terhadap Keputusan Berkunjung Di Objek Wisata Puncak Lawang - Yasnida, Yasnida; Kartini, Kartini; Mardoni, Afrizal (Jurnal Penelitian Dan Pengkajian Ilmiah Sosial Budaya, 2025)
The existence of tourist attractions in Puncak Lawang is a special attraction for the existence of tourist attractions in Puncak Lawang, especially those who want to enjoy the natural atmosphere at Puncak Lawang. The purpose of this study was to determine the effect of attractiveness, accessibility and facilities on the decision to visit the Puncak Lawang tourist attraction. The object of this study was at Puncak Lawang which is located in Agam Regency. The population in this study were consumers who had visited the Puncak Lawang tourist attraction with an unknown number. According to Rosoe's theory (2012) that for the sample is 10 x the number of research variables, namely 10 x 4 = 40 samples. So the number of samples in this study is 40 respondents. The results of this study The tourist attraction variable has a significant effect on the decision to visit the Puncak Lawang tourist attraction. This is evidenced by the t-count value of 2.780 which is greater than the t-table of 1.68385 (2.789> 1.68385) with a significance level of 0.008 meaning less than 0.05 (0.008 <0.05). The accessibility variable has a significant effect on the decision to visit the Puncak Lawang tourist attraction. This is evidenced by the t-count value of 2.216 which is greater than the t-table of 1.68385 (2.216> 1.68385) with a significance level of 0.033 meaning less than 0.05 (0.033 <0.05). The facility variable has a significant effect on the decision to visit the Puncak Lawang tourist attraction. This is evidenced by the t-value of 2.606 which is greater than the t-table of 1.68385 (2.606> 1.68385) with a significance level of 0.013 meaning it is less than 0.05 (0.013 <0.05). The variables of tourist attraction, accessibility and facilities have a significant effect on the decision to visit the Puncak Lawang tourist attraction. This is evidenced by the F-value of 16.101> F-table 2.86 with sig = 0.000 <0.05. The variables of tourist attraction, accessibility and facilities have a joint contribution of (0.573 x 100%) = 57.3% to the dependent variable, namely the decision to visit (Y) while the rest (100% - 57.3%) = 42.7% of the decision to visit is influenced by other variables not examined in this study.